PENGEMBANGAN RITATOON BERBASIS QR-CODE BERBANTUAN VIDEO UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS V SEKOLAH DASAR - Salsabela Dima Ayu Fitriana; Novi Setyasto (Program Studi PGSD Universitas Flores, 2023)
Social studies learning can run effectively and efficiently with the support of creative and innovative media. Based on pre-research data at SDN 1 Pegulon, a problem was found in the form of the use of learning media that was not optimal, especially in the use of technology, most students passive and affecting low learning outcomes. The study population was 49 students consisting of 43 students of SDN 1 Pegulon and 6 students of SDN Pagerdawung. This study aims to develop, test the feasibility and test the effectiveness of video-assisted QR-Code-based Ritatoon media in the social studies content of grade V SDN 1 Pegulon. The type of research is research and development with the development model, namely Borg and Gall. Data collection techniques in the form of tests and non-tests. The results showed that the media developed was very feasible as evidenced by the assessment of media experts with a percentage of 100% and material experts of 85.71%. Effective media to improve student learning outcomes is shown from the results of the t-test with sig. (2-tailed) of 0.000<0.05 and the N-gain average increase test of 0.557 with moderate criteria. The media received positive responses from teachers by 89.7% and students by 87%. The conclusion of this study is that video-assisted QR-Code-based ritatoon media is very feasible and effective to use in learning social studies in grade V.